Verbal and Non-Verbal Violence in Films “Dilan 1990, 1991 and Milea: Dilan's voice” - Darell Abhirama Abrar; Noer Nazwa M (Cakra Communico: Journal of Communication Science, 2024)
This film is adapted from the novel entitled "Dilan: He is My Dilan in 1990" written by Pidi Baiq and directed by Fajar Bustomi. The film Dilan tells the story of teenage love among high school students in the city of Bandung. Behind this romantic story, there is a lot of controversy that has arisen in society regarding the violent scenes that occur in this Dilan film . Dilan is a member of a famous motorbike gang in the city of Bandung and Milea is a student who has just moved to Bandung. There are several scenes in this film that show verbal and non-verbal violence. Non-verbal violence includes physical violence and verbal violence is a form of violence that is characterized by speech in this film, which is represented by words such as flirt, devil, etc. This research aims to conduct a quantitative analysis of the influence of violence against teenagers in the film "Dilan 1990" on audience perceptions. The method used in this research is a quantitative method. Quantitative methods are used to measure how much violence occurs in the Dilan film objectively, systematically and quantitatively describing the contents of statements in a communication that is clearly visible. In this research, we will find out the frequency and percentage of violent scenes in teenagers who were studied using quantitative methods. This quantitative content analysis study was carried out to describe that the verbal violence in the film Dilan has various elements of a message to be conveyed to the film 's viewers . . This research was conducted using quantitative content analysis methods. The results of this research show that the violence that appears is verbal violence ( 50 %), and non-verbal violence ( 26 %).